5 Years of Must Reads from HBR - Review, Harvard Business. (HBR's 10 Must Reads., 2023)
Five years' worth of management wisdom, all in one place. Get the latest, most significant thinking from the pages of Harvard Business Review in 5 Years of Must Reads from HBR: 2024 Edition. Every year, HBR editors examine the ideas, insights, and best practices from the past twelve months to select the definitive articles that have provoked the most conversation and inspired the most change. From managing in the age of outrage, to getting more out of your AI initiatives, to running the perfect one-on-one meeting, the articles in this five-book collection will help you manage your daily challenges and meet the changing competitive landscape head-on. Books in HBR's 10 Must Reads series offer essential reading selected from the pages of Harvard Business Review on topics critical to the success of every manager. Each book is packed with advice and inspiration from leading experts, such as Satya Nadella, Frances X. Frei, Marcus Buckingham, Adam Grant, Joan C. Williams, Roger Martin, Robert Livingston, and Katrina Lake. Company examples range from P&G, UPS, and Pfizer to Alibaba, Microsoft, and Stitch Fix. 5 Years of Must Reads from HBR: 2024 Edition brings the most current and important business conversations to your fingertips. HBR's 10 Must Reads paperback series is the definitive collection of books for new and experienced leaders alike. Leaders looking for the inspiration that big ideas provide, both to accelerate their own growth and that of their companies, should look no further. HBR's 10 Must Reads series focuses on the core topics that every ambitious manager needs to know: leadership, strategy, change, managing people, and managing yourself. Harvard Business Review has sorted through hundreds of articles and selected only the most essential reading on each topic. Each title includes timeless advice that will be relevant regardless of an ever-changing business environment.